Review of Pierrepont, Alexandre. 2015. La Nuée. L’AACM: Un Jeu de Société Musicale. Marseille: Éditions Parenthèses. - Citton, Yves (Current Musicology, 2017)
The Association for the Advancement of Creative Musicians (AACM), which recently celebrated its 50th birthday, is certainly one of the most important musical movements of the twentieth and twenty-first centuries. This much we know. This thick and dense book, written by French an-thropologist and musical theorist Alexandre Pierrepont over a period of almost twenty years, demonstrates that, on top of inventing new ways to make music, the members of the AACM also invented better ways to make a society. Subtitled A Game-Play of Musical Society, it offers a profound and joyous analysis of the many strata simultaneously developed in Chicago beginning in 1965 by African American musicians who had no alternative but to invent new social relations in order to survive economically and thrive artistically as creators, in a country doubly biased against African Americans and against artistic experimentations and lifestyles.